The Voice of Our Sister to the Frenemy among Us: Psalm 55 - Reid, Stephen Breck (Interpretation, 2024)
The violence and discord of contemporary experience find resonance in Psalm 55. Awareness of multiple voices in the psalm reveals nuances in the rhetoric of violence and discord as microaggressions and acts of more explicit violence and abuse, including murder. Psalm 55 includes the language of taunt and insolence, what we sometimes refer to in contemporary parlance as gaslighting. The language of the sword represents not only war but intimate violence and abuse. The careful reader of Psalm 55 finds multiple voices in the ancient past that prefigure and amplify multiple voices in the conflicted present.